2004
DOI: 10.1530/rep.1.00169
|View full text |Cite
|
Sign up to set email alerts
|

The cytosolic sperm factor that triggers Ca2+ oscillations and egg activation in mammals is a novel phospholipase C: PLCζ

Abstract: fertilization. One theory suggests that sperm initiate signals to activate the egg by introducing a specific factor into the egg cytoplasm after membrane fusion. This theory has been mainly based upon the observation that injecting a cytosolic sperm protein factor into eggs can trigger the same pattern of Ca 21 oscillations induced by the sperm. We have recently shown that this soluble sperm factor protein is a novel form of phospholipase C (PLC), and it is referred to as PLCz(zeta). We describe the evidence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
89
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(94 citation statements)
references
References 62 publications
(43 reference statements)
0
89
0
4
Order By: Relevance
“…Subsequent IP 3 binding to its own receptor on the endoplasmic reticulum (ER) [19] opens Ca 2+ channels, which release Ca 2+ from the ER into the cytoplasm of the oocyte [19]. The resulting Ca 2+ oscillations within the oocyte [18,19] disseminate from the cortical region throughout the ooplasm [20,21] at 10-to 20-min intervals [22], triggering oocyte activation [23] to initiate oocyte fertilization and preimplantation embryogenesis [8,14,17].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent IP 3 binding to its own receptor on the endoplasmic reticulum (ER) [19] opens Ca 2+ channels, which release Ca 2+ from the ER into the cytoplasm of the oocyte [19]. The resulting Ca 2+ oscillations within the oocyte [18,19] disseminate from the cortical region throughout the ooplasm [20,21] at 10-to 20-min intervals [22], triggering oocyte activation [23] to initiate oocyte fertilization and preimplantation embryogenesis [8,14,17].…”
Section: Discussionmentioning
confidence: 99%
“…Quick disintegration of the sperm plasma membrane within the oocyte is important because oocyte activation depends on sperm-borne oocyte-activating factor (SOAF). The strongest candidate for SOAF in mammals thus far is phospholipase C- (17)(18)(19)(20). At least part of SOAF is localized in the perinuclear theca in the postacrosomal region (21)(22)(23)(24) and under the plasma membrane over the equatorial segment of the acrosome (25).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, epigenetic factors related to early paternal effects on embryo development have been reported. These include factors such as phospholipase C-ζ(PLCζ), which are responsible for regulating calcium oscillations necessary for oocyte activation, but their mechanisms of action are not clearly understood (15). It has been shown that mouse oocyte calcium oscillations are promoted in the presence of PLCζ and are depleted in its absence (15).…”
Section: Discussionmentioning
confidence: 99%
“…These include factors such as phospholipase C-ζ(PLCζ), which are responsible for regulating calcium oscillations necessary for oocyte activation, but their mechanisms of action are not clearly understood (15). It has been shown that mouse oocyte calcium oscillations are promoted in the presence of PLCζ and are depleted in its absence (15). Furthermore, the sperm derived centrosome was shown to be the only functionally active centrosome in the early stages of embryogenesis.…”
Section: Discussionmentioning
confidence: 99%